Graphene-based cardiac sensors and actuators - Savchenko, Alex; Kireev, Dmitry; Yin, Rose T.; Efimov, Igor R.; Molokanova, Elena (Frontiers in Bioengineering and Biotechnology, 2023)
Graphene, a 2D carbon allotrope, is revolutionizing many biomedical applications due to its unique mechanical, electrical, thermal, and optical properties. When bioengineers realized that these properties could dramatically enhance the performance of cardiac sensors and actuators and may offer fundamentally novel technological capabilities, the field exploded with numerous studies developing new graphene-based systems and testing their limits. Here we will review the link between specific properties of graphene and mechanisms of action of cardiac sensors and actuators, analyze the performance of these systems from inaugural studies to the present, and offer future perspectives.